TEMPORAL FRAMES FOR PLATFORM PUBLICS: THE PLATFORMIZATION OF BREADTUBE - Mniestri, Aikaterini; Gekker, Alex (AoIR Selected Papers of Internet Research, 2020)
In this paper we suggest the notion of platform publics to account for the intermingling of socio-technical processes that make online platforms (in this case: YouTube) resistant to stable definitions. It has been over a decade of YouTube studies and yet, a consensus on what precisely YouTube is seems unlikely. Arguably, Burgess and Green began this ontological quest with the first edition of YouTube (2008) in which they set out ‘to work through some of the often-competing ideas about just what YouTube is.” (iv) Snickars and Vondereau (2009) considered the “ontological ambivalence” (2009, p. 28) of YouTube to be an asset since the platform’s success was rooted in its flexibility as a stage for content. Following work attempted to understand YT as a ‘new screen ecology’ (Cunningham 2016); through its platform logics of monetization and viewership (Postigo 2015, Van Es 2020); as a contested space between creators, content and audience (Berryman and Kavka 2018, Bishop 2018; 2019); and as a database, often implementing scraping and other computational techniques to account for its nature as vast graph network of content (Airoldi et al. 2016) with internal algorithmic dynamic - for instance the preference of “YT-native” content over mainstream actors within its search and recommendations (Rieder et al. 2018). We abandon the ontological stability of YT as singular and instead present it from a post-representational (Thrift 2008) and temporally-orientated (Adam 2008) perspective. Using BreadTube as a case study, we refrain from asking what YT is, but rather where and when YT happens.